2010
DOI: 10.3139/217.2335
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Erosion Wear Response of SiC Filled Epoxy Composites Reinforced with Glass and Bamboo Fibers

Abstract: The present work describes the processing and studies the erosion wear characteristics of bamboo fiber reinforced epoxy composites filled with SiC particulate. The mechanical properties of these composites are evaluated and are then compared with those of a similar set of SiC filled glass-epoxy composites. The solid particle erosion characteristics of the bamboo-epoxy composites have also been studied and the experimental results are compared with the reported erosion test results on glassepoxy composites unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In contrast, the erosion rate increased appreciably on further increasing the erodent size from 175 μm to 275 μm, and on further increasing the erodent size from 275 μm to 350 μm, the erosion rate starts decreasing. As reported by Biswas and Satapathy [38,39] and Patnaik et al [40], for glass fiber-reinforced polymer composites, with the increase in erodent size, the erosion rate increases gradually irrespective of fiber loading. It is also observed that the composite with 40 wt% of bamboo fiber loading shows most erosion resistant closely followed by the composite with 20 wt%, 30 wt%, and 10 wt% of bamboo fiber loading.…”
Section: Effect Of Impact Velocity On Erosionmentioning
confidence: 53%
“…In contrast, the erosion rate increased appreciably on further increasing the erodent size from 175 μm to 275 μm, and on further increasing the erodent size from 275 μm to 350 μm, the erosion rate starts decreasing. As reported by Biswas and Satapathy [38,39] and Patnaik et al [40], for glass fiber-reinforced polymer composites, with the increase in erodent size, the erosion rate increases gradually irrespective of fiber loading. It is also observed that the composite with 40 wt% of bamboo fiber loading shows most erosion resistant closely followed by the composite with 20 wt%, 30 wt%, and 10 wt% of bamboo fiber loading.…”
Section: Effect Of Impact Velocity On Erosionmentioning
confidence: 53%
“…Constituents of the composite retain their individual physical and chemical properties significantly whereas together they combine to make up the qualities that one constituent cannot produce while alone. Reinforcements have been made of inorganics (synthetic fibre) such as glass, carbon and amid [3].…”
mentioning
confidence: 99%